Redox‐Neutral Metal‐Free Three‐Component Carbonylative Dearomatization of Pyridine Derivatives with CO2. Issue 67 (7th November 2019) - Cerveri, Alessandro; Pace, Stefano; Monari, Magda; Lombardo, Marco; Bandini, Marco
Abstract: The TBD (1, 3, 5‐triazabicyclodec‐5‐ene) assisted three‐component carbonylation of pyridine‐2‐methanamines is documented by means of CO2 as a benign CO surrogate. The redox‐neutral methodology enables the realization of densely functionalized imidazo‐pyridinones in high yields (up to 93 %) and excellent chemoselectivity. Combined computational and experimental investigations revealed an unprecedented RCOCl/TBD concerted electrophilic activation of carbon dioxide. Abstract : Three is better than two ! A three‐component metal‐free carbonylative dearomatization of pyridine derivatives is documented with CO2 as a CO surrogate. A range of imidazo‐pyridinones are obtained in high yield (up to 93 %) through an unprecedented RCOCl/TBD concerted electrophilic activation of carbon dioxide (see scheme).